Enabling dynamic positioning of floating tidal turbines in an open regional-scale 3D hydrodynamic model (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Floating tidal turbines typically move in six degrees of freedom - heave, pitch, roll, surge, sway and yaw - in response to the coupling effects of wind, waves and current. Despite extensive work on floating turbine motion and wake dynamics using Computational Fluid Dynamics simulation and laboratory experiments, no study to date has incorporated dynamic translation of floating turbines in regional-scale 3D hydrodynamic models. This study addresses this knowledge gap by demonstrating a technique in Telemac3D to dynamically translate a conceptual twin-rotor floating turbine with a simplified setup. The turbine is modelled via actuator discs in an idealised rectangular channel with time-varying inflow. A scenario of surging and swaying motions is examined, from which the turbine follows a user-defined path with maximum surge and sway amplitudes of 20m and 5m respectively. The rotor positions are updated dynamically within the simulation as the flow speed in the domain changes. Simulation results confirm that the technique effectively captures both the movement of the turbine and its wake. Although small discrepancies in hub-height velocity deficits between individual rotor wakes immediately downstream indicate limitations in current rotor volume discretisation and thrust distribution method for the dynamically moving turbine, the work completed to date provides a foundation for integrating dynamic floating turbine positioning with multiple degrees of freedom into large spatial-scale 3D hydrodynamic models.